Determinants of ICT innovations: Lessons learned from Sweden and Sri Lanka - Chaminda Wijesinghe; Henrik Hansson; Love Ekenberg (Administrative Sciences, 2021)
Innovation is critical for enterprises and the country's economy, and it has resulted in an improvement in living standards. There may be appropriate lessons to learn from other countries, but their adoption must be assessed due to education and living standards variations. This paper aims to build an in-depth understanding of the stimulating factors for ICT innovations from Sweden, and examines their adoption in the context of a developing country, Sri Lanka. ICT innovations significantly impact development in other sectors, as they can ease doing business and other essential services. This study is based on seven interviews, including key people leading innovation activities in Sweden. Then, it critically analyses and presents the application of stimulating factors in Sweden to the context of a developing country, namely Sri Lanka. The results indicate that education and mindset, a risk-taking environment, embracing failures, digitalisation and collaboration are the critical determinants of ICT innovations in Sweden. This research is vital for educational policymakers in universities, technology transfer offices, and governmental policymakers.
Keywords: 350; collaboration; determinants; developing country; innovation; Sri Lanka; Sweden